A study on the effectiveness of marketing strategy implemented by Pesakabumi Industries Sdn. Bhd. / Najdah Abd Aziz - Abd Aziz, Najdah (1999)
Pesakabumi Corporation Sdn. Bhd. is presently operating on a 20-acre factory complex comprising of several office buildings, furniture workshops, truss fabrication plants, disposable gas lighter factory and chemical impregnation chamber for treatment of sawn timber and storage. It is situated at Seberang Marang, Terengganu, about five kilometers north of the proposed Pulau Kerengga Industrial Estate. While Pesakabumi Industries Sdn. Bhd. was involved in timber related industries since 1965. With more than 30 years in the Wood and Furniture Manufacturing Industry, Pesakabumi Industries Sdn. Bhd. had succeeded in gaining a lot of expertise and experience that enabling the company to become a more professional organization in this field. Various tech and technology, both old and new are utilized in the production to ensure that every product churned out fits and meets its specifications. Initially, the purpose of this research is to evaluate the effectiveness of marketing strategy since it was implemented in Pesakabumi Industries Sdn. Bhd. So the researcher will analyze the way on how marketing strategy can be implemented and also compared it with the others companies in the same field. Marketing strategy be important things to the company especially when it involved export and import business. It can be as a guideline for the company in dealing with the others. So it must be set properly and completely as it covered